2003
DOI: 10.1248/cpb.51.608
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 6-Substituted 9-Benzyl-8-hydroxypurines with Potential Interferon-Inducing Activity

Abstract: Various 6-substituted 9-benzyl-8-hydroxypurines were synthesized in order to investigate the structure-activity relationship at the 6-position of 9-benzyl-8-hydroxyadenine (1), which is a lead compound for the screening of interferon (IFN)-inducing activity. 6-Unsubstituted, mercapto-, methylthio- and hydroxy-9-benzyl-8-hydroxypurines (2-5) were prepared from 5-amino-1-benzyl-4-cyano-2-hydroxyimidazole (9). Synthesis of a 6-methoxy analog (6) was conducted from 5-amino-4-benzylamino-6-chloropyrimidine (13). 6-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Critical for this work, N -methylation of 26 , to give 27 , is observed to completely ablate TLR7 activity in this series and also results in a modest increase in MTH1 affinity. This observation has previously been reported for a closely related series of TLR7 agonist purinones and indicates that the exocyclic NH 2 motif is critical for TLR7 activity . In a similar fashion, it has been reported that N -methylation of 4 also results in complete loss of TLR7 agonist activity .…”
Section: Resultssupporting
confidence: 81%
“…Critical for this work, N -methylation of 26 , to give 27 , is observed to completely ablate TLR7 activity in this series and also results in a modest increase in MTH1 affinity. This observation has previously been reported for a closely related series of TLR7 agonist purinones and indicates that the exocyclic NH 2 motif is critical for TLR7 activity . In a similar fashion, it has been reported that N -methylation of 4 also results in complete loss of TLR7 agonist activity .…”
Section: Resultssupporting
confidence: 81%
“…In addition to the ability to form water-soluble salts, the 4-piperidinyl moiety of oxoadenines 3a–g also provides a suitable handle for potential N-derivatization and conjugation as substitution of the aromatic amino group in both the oxoadenine and imidazoquinoline series abolishes IFN-inducing activity. 6,17 Conjugation of TLR7/8 agonists to lipids, proteins, and other molecules is known to enhance immune responses and decrease toxic effects. 6,18,19 …”
mentioning
confidence: 99%
“…The next step of the synthesis consisted of forming the cyclic urea of the purin-8-one skeleton. This was conveniently achieved in quantitative yields by using triphosgene 12 in THF (Scheme 1, 5a,c-g, Table 1). Whereas triphosgene reacted rapidly with the first amino functionality (presumably the more nucleophilic 5-amino substituent) at room temperature to form a non-cyclised intermediate, 13 heating to reflux was required for complete cyclisation into purin-8-ones 5.…”
Section: Figurementioning
confidence: 99%